Lessons learned from a multi-site collaborative working toward a digital health use screening tool - Hernandez, Ann M.; Khoong, Elaine C.; Kanwar, Neytali; Lopez-Solano, Naomi; Rodriguez, Jorge A.; De Marchis, Emilia; Nguyen, Oanh Kieu; Casillas, Alejandra (Frontiers in Public Health, 2024)
Digital health has the potential to expand health care and improve outcomes for patientsparticularly for those with challenges to accessing only in-person care. The acceleration of digital health (and particularly telemedicine) prompted by the Coronavirus-19 (COVID-19) pandemic facilitated continuity of care in some settings but left many health systems ill-prepared to address digital uptake among patients from underserved backgrounds, who already experience health disparities. As use of digital health grows and the digital divide threatens to widen, healthcare systems must develop approaches to evaluate patients' needs for digital health inclusion, and consequentially equip patients with the resources needed to access the benefits of digital health. However, this is particularly challenging given the absence of any standardized, validated multilingual screening instrument to assess patients' readiness for digital healthcare that is feasible to administer in already under-resourced health systems.